Toward effective protection of victims of human trafficking in mixed migration flows: referral mechanisms shaped on individual need. The Italian experience and the European perspective - Nicodemi, Francesca; Cirillo, Chiara (Frontiers in Human Dynamics, 2024)
An overview of emerging trends on trafficking of human beings in Italy shows not only an extremely heterogeneous phenomenon but also a complex overlapping of experiences and need of protection of every single victim. In the context of mixed migration flows, persons reaching Italy through the Central Mediterranean and the Balkan routes have often experienced or are at risk of trafficking, and they also apply for international protection upon arrival. Legal categories such as “victims,” “asylum seekers,” and “refugees” are increasingly interconnected and not exhaustive in describing individual experiences and multifaceted vulnerabilities. Against this background, ensuring early identification and assistance for victims of trafficking among asylum seekers is extremely relevant. In Italy, this has led to the development of good practices aimed at implementing the coordination between the asylum and the anti-trafficking systems. In particular, specific Guidelines for Asylum authorities have been adopted to preliminarily identify potential victims of trafficking within the asylum procedure and enable their effective access to protection measures. To comply with specific provisions of the European Trafficking Directive and its transposition into the Italian legal framework, the Guidelines have created a referral mechanism among the asylum authorities and the anti-trafficking system that is unique in the European context. For this reason, the present contribution aims at describing this good practice, its implementation and effects—also at the juridical level—and its limits. Indeed, after the adoption of the instrument, a higher recognition rate of international protection for victims of trafficking has been registered in Italy, both at the administrative and judicial levels; asylum seekers and refugees have also increased their access to the specific protection program for trafficking survivors. In general, the system has strengthened its capacity to fulfill the legal obligation of identifying victims through a multi-agency approach. On the other hand, the ability to conduct screening and preliminary identification of victims of trafficking among asylum seekers is still limited to the “victim model” in terms of gender (women) and form of exploitation (sexual), and to certain stages of the asylum procedure (the first instance before the asylum authorities). With reference to this latter, a comprehensive protection response at the borders is missing despite the political debate on sea and land arrivals to Italy and the recent introduction of border procedures for the assessment of asylum applications. Given the geographical and political centrality of the south-Mediterranean situation in the current migration agenda, the goal of this paper is to analyze the Italian experience on referral mechanisms among trafficking and asylum as an experience that would help to shape future European prospects. The ongoing evolution of mixed migration flows—with particular reference to secondary movement across European countries—and the revised European Directive on trafficking in persons impose the promotion of a reflection on referral mechanisms with a transnational perspective enabling effective protection and the meeting of specific human rights.